THE EFFECT OF GIVING MANGROVE LEAVES EXTRACT Rizhophora apiculata ON GROWTH PERFORMANCE OF VANAME SHRIMP - Junaidi, Muhammad; Azhar, Fariq; Setyono, Bagus Dwi Hari; Waspodo, Saptono (Buletin Veteriner Udayana, 2020)
Constraints, that are often faced by farmers, are pests and diseases that can reduce shrimp quality and production failure. Diseases that often attack shrimp are bacterial diseases such as vibriosis. The bacterial disease is usually treated using antibiotics. In this study, the antibiotic used was derived from Rhizophora apiculata mangrove leaf extract which contained active compounds as antibacterial. The use of R. apiculata mangrove leaf extract is expected to be able to improve the growth performance of white shrimp through enhancing the immune system. This study aims to determine the effect of R. apiculata mangrove leaf extracts on the growth performance of white shrimp ( Litopenaeus vannamei ). This research was conducted for 40 days. The treatment given was the addition of R. apiculata mangrove leaf extract into shrimp feed namely P1 control without the addition of extract, P2 was given 0.5% mangrove extract, P3 was given 1% mangrove extract and P4 was given 2% mangrove extract. The results obtained for the growth performance of the best treatment white shrimp on P4 (feed + mangrove extract 2%) with the results of absolute weight growth of 17.41 g, specific growth of 21.37%, survival of 93% and feed conversion of 1, 1 R. apiculata mangrove leaves can improve the growth performance of white shrimp through absolute weight growth, specific growth rate, survival and feed conversion ratio values, the best value is obtained at 2% extract dose with each value of 17.31 g, 21.37%, 93%, and 1.1%.